Exploration of New Complexity Metrics for Curriculum-Based Measures of Writing. (September 2019) - Wagner, Kyle; Smith, Alex; Allen, Abigail; McMaster, Kristen; Poch, Apryl; Lembke, Erica
Researchers and practitioners have questioned whether scoring procedures used with curriculum-based measures of writing (CBM-W) capture growth in complexity of writing. We analyzed data from six independent samples to examine two potential scoring metrics for picture word CBM-W (PW), a sentence-level CBM task. Correct word sequences per response (CWSR) and words written per response (WWR) were compared with the current standard metric of correct word sequences (CWS). Linear regression analyses indicated that CWSR predicted scores on standardized norm-referenced criterion measures in more samples than did WWR or CWS. Future studies should explore the capacity of CWSR and WWR to show growth over time, stability, diagnostic accuracy, and utility for instructional decision making.